Comparison of Educational and Learning Innovations in Secondary Education Units - Susilowati, Rini; Hendrayana, Endri; Abdul Hamid, Eka; Waska Warta; Cepi, Ujang (International Journal of Educational Research & Social Sciences, 2022)
The reason for this research was to determine the difference between educational and learning innovations at SMKN 1 Buahdua and SMKS Pelita Bunga Bangsa. The research method was carried out with a descriptive and comparative approach. For the specified sample, namely the academic community of SMKN 1 Buahdua and SMKS Pelita Bunga Bangsa. The data used are primary data with the instrument in the form of a questionnaire. The aftereffects of the combined sample T test for educational innovation, show the worth of Sig. (2-tailed) of 0.137 > 0.05, then there is no difference between educational innovation at SMKN 1 Buahdua and SMKS Pelita Bunga Bangsa. Educational innovations carried out by SMKN 1 Buahdua focus on supporting educational infrastructure. Meanwhile, educational innovation at SMKS Pelita Bunga Bangsa focuses on aspects of curriculum and learning management. Furthermore, the results of the paired sample T test for learning innovation, show Sig. (2-tailed) of 0.140 > 0.05, then there is no difference between learning innovation at SMKN 1 Buahdua and SMKS Pelita Bunga Bangsa. Learning innovation at SMKN 1 Buahdua is more emphasized on the implementation of learning and communication with students through social media. While the learning innovations at SMKS Pelita Bunga Bangsa include several things, namely; carry out learning in schools, communicate with students through social media, in terms of delivering lessons, then in the use of study time, in grouping lessons, in preparing lesson plans, in defining problems that occur in learning, and in collecting all the data needed in learning.